Characteristics of Curds With Milk Clotting Enzyme from Indonesian Local Isolate of Lactic Acid Bacteria - Putranto, Wendry; Mustopa, Apon; Mamangkey, Jendri; Aritonang, Netty (Publisher Cv. Inara, 2020)
To get the potential of lalcat acid bacteria isolate to produce Milk Clotting Enzyme (MCE), it is necessary to screen milk clotting activity both quantitatively and qualitatively. Through qualitative observation, the characteristics of the curd resulting from enzyme activity can be obtained. MCE is a protease that has the characteristics of milking. Based on the results of this observational research, the curd characteristic produced can be used as a benchmark to determine the length of time of fermentation and optimization of the determination of ammonium sulfate precipitation concentration. Isolate BAL shows the results of a compact curd at a fermentation time of 25 hours at 37 ? and the optimization results of the deposition of ammonium sulfate which shows the characteristics of a compact curd by 45% ammonium sulfate.